Pulmonary alveolar proteinosis following cryptococcal meningitis: a possible cause?. (28th March 2018) - Demir, Sarah; Chebib, Nader; Thivolet-Bejui, Francoise; Cottin, Vincent
Abstract : Autoimmune pulmonary alveolar proteinosis (PAP) is a rare interstitial lung disease characterised by the presence of granulocyte macrophage colony-stimulating factor (GM-CSF) autoantibodies. A man with no history of infection developed cryptococcal meningitis and a right parahilar cryptococcal mass. Antifungal treatment led to infection control, although there was presence of neurological sequelae. After 3 years, thoracic CT revealed bilateral ground glass opacities and a crazy paving pattern. Transparietal needle biopsy showed proteinaceous alveolar deposits, confirming the diagnosis of PAP. A high titre of serum anti-GM-CSF autoantibodies was found. No specific treatment was started, and radiological lesions decreased progressively. Cryptococcal infection may occur in PAP and in patients with anti-GM-CSF antibodies without PAP. These antibodies dysregulate phagocytosis in monocytes and macrophages, possibly leading to opportunistic infections in previously healthy subjects.